Biologia, África e identidades sociais: a representação produzida pelos discursos sobre genética e evolução em livros didáticos - Silvério, Florença Freitas (Universidade Federal de São Carlos, 2021)
In this research I investigated how the genetics and evolution discourses was affect by the legal apparatus of 10.639/2003 law and National Curricular Guidelines for Education of Ethnic-Racial Relations and for History Teaching and Afro-Brazilian and African Culture (DCNERER - initials in portuguese). The objective was study the school genetics and evolution discourses, in the context of discussions about the curriculum as representation and its (possible) transformations because of the demand for more justice within racial relations. To do thar I examined the african continent representation and “race”, “ethnicity” and skin color representations in the genetics and evolution discourses in Biology textbooks. Gathering together some elements of the curricular area – especially the Michael Apple, Henry Giroux and Tomás Tadeu da Silva’s contributions –, of Cultural Studies – especially Stuart Hall’s contributions – and of education of ethnic-racial relations – especially Nilma Lino Gomes’s contributions -, I did an analysis of genetics and evolution discourses with the articulation of content analysis, propose by Bardin (2011) conjugated with discourse analysis systematized by Orlandi (2015). From Cultural Studies poststructuralism perspective concepts, as representation, identity and difference, I examined how this discourses produces meanings about Africa, skin color, “race” and “ethnicity”; to discuss how the representation was affect over time by DCNERER; and how the representations can contribute for education of ethnicracial relations. In this research, I adopted a social constructivism perspective about culture e representation, as Hall (2016), where representation is a practice, a work, an action and not a reflect of the real. In this perspective, identity and difference are culture facts, makes in the social relations and not natural facts. Then, I found that the genetics and evolution discourses produce racialized representations regimes, compose by stereotypes about de african continent and by the objectivization the social identity. The genetics and evolution discourses produce the homogenous, primitive and wild Africa representation, oppositional with a civilized Europe. Furthermore, the “race”, “ethnicity” and skin color ideas are produced as biology facts that mark the natural difference, removing its of its social contexts of identity produce. This regime was move after the DCNERER, however don’t show in full that proposed for guidelines, was privileged cosmetic and descontextualized changes, that don’t came back your attention for the power structures that produce and keep the racism in society.
Biology, Africa and social identities: the representations produced by genetics and evolution discourses in textbooks
Keywords: Educação das relações étnico-raciais; Currículo; África; Identidade; Diferença; Education of ethnic-racial relations; Curriculum; Africa; Identity; Diference; CIENCIAS HUMANAS::EDUCACAO::CURRICULO